2010
DOI: 10.2106/jbjs.h.01600
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Serum Procalcitonin Level for Differentiation of Infectious from Noninfectious Causes of Fever After Orthopaedic Surgery

Abstract: Serum procalcitonin is a helpful diagnostic marker supporting clinical and microbiological findings for more reliable differentiation of infectious from noninfectious causes of fever after orthopaedic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 37 publications
0
51
1
6
Order By: Relevance
“…Moreover, serum PCT level was proclaimed as a significant predictor for postoperative infection. 17,18 Diagnostic test showed that the sensitivity and specificity of serum PCT level in detecting SSI was higher than those of leucocyte count in this study. This result is in line with previous studies reported by some authors.…”
contrasting
confidence: 51%
See 1 more Smart Citation
“…Moreover, serum PCT level was proclaimed as a significant predictor for postoperative infection. 17,18 Diagnostic test showed that the sensitivity and specificity of serum PCT level in detecting SSI was higher than those of leucocyte count in this study. This result is in line with previous studies reported by some authors.…”
contrasting
confidence: 51%
“…Serum PCT level showed a better predictor than leucocyte count to detect an infection caused by S. negative-coagulase growth. 22 Although many studies reported that serum PCT level had a high predictive value in detecting infection after surgery, [18][19][20][21][22] however, a study conducted in patients who underwent elective spinal urgery gave different result, as serum PCT level in general remained at <0.25 ng/mL during the postoperative course. Moreover, serum PCT level did not correlate with age, sex, DM, hypertension, BMI, operation time, operation site, or use of instrumentation.…”
mentioning
confidence: 99%
“…Others have found sensitivity and specificity values for procalcitonin in similar ranges (Table 3) [2,5,11,14,21,26,29,30,33]. However, the results reported by Worthington et al were quite different: serum procalcitonin did not help distinguish between infectious and noninfectious causes of prosthetic hip loosening [41].…”
Section: Discussionmentioning
confidence: 91%
“…Numerous studies have shown procalcitonin is elevated in cases of bacterial infection or sepsis and levels are considerably higher in bacterial infections than in viral infections [2,5,11,14,21,26,29,30,33]. Procalcitonin increases 2 to 4 hours after the onset of sepsis, which is later than proinflammatory cytokines, such as interleukin 6 (IL-6), but considerably earlier than CRP [31].…”
Section: Introductionmentioning
confidence: 99%
“…5 Measurement of PCT in particular has gained interest because it is a quantitative test that exhibits predictable value and is more responsive to postoperative events compared with CRP and ESR. [6][7][8] Nevertheless, in current clinical practice, PCT are not widely used as routine screening tests in the early postoperative period, with most surgeons relying on the leukocyte count, CRP and ESR despite evidence that these are poor diagnostic tests. 9 PCT was already used in several other studies to predict postoperative infections after several different operations, [5][6][7][8]10,11 however, the predictive value of serum PCT in detecting postoperative infectious complications in spinal cord injury patients has not been studied.…”
Section: Introductionmentioning
confidence: 99%